How Do Accounting Students Respond to Integrated Learning In Sustainability Accounting? - Kurniawan Saputra, Komang Adi; Putri, Putu Yudha Asteria; Laksmi, Putu Ayu Sita (Fakultas Ekonomi Universitas Negeri Manado, 2024)
The aim of this research is to analyze the content of the curriculum and the messages conveyed by students in order to adapt the integrated curriculum for sustainability accounting courses. The research method used is content analysis which uses information from key informants as research data. In addition, a survey was conducted on sixty students taking social and environmental accounting courses. The sampling technique was carried out using simple random sampling. The results of the research are that sustainability accounting is considered important to be implemented in the accounting education curriculum at bachelor's and master's levels. Students are interested in sustainability accounting because it is a new paradigm in the field of accounting which focuses on social and environmental transactions. The main contribution of the research is aimed at improving the accounting study program curriculum to adopt sustainability accounting as a separate course following the development of the accounting profession.